Antimicrobial Activity of the Extract of Garlic and Onions - M, Abdel-Rahim A.; Idris, Abdel-Malik O. A.; E, Sulieman A. (Gezira Journal of Engineering and Applied Sciences, 2018)
This study investigated the pathogenicity of two fungi ( A. niger and P .digitatum ) and two bacteria ( S. aureus and E. carotovora ) on onion bulbs. The inoculated areas of the onion bulbs showed changes in their colour and the tissues macerated then an offensive smell developed. The three onion bulbs responded similarly. The non-autoclaved red onion extracts reduced radial growth of both fungi more than the autoclaved onesThe results on the radial growth indicated that the onion extracts were highly effective at the higher concentration (0.01, 0.1 and 1.0) compared to the lower concentration (0.001) and the control (0.00). Garlic extract at the higher concentration completely inhibited radial growth of both fungi.The yellow onion extract caused a reduction of mycelial dry weight of A. niger to about 60.46, 31.09, 23.04 and 5.95% at the concentrations 1.0, 0.1, 0.01 and 0.001, respectively. The white onion extract gave a reduction of about 38.77, 34.55, 20.73 and 4.41% at the concentrations 1.0, 0.1, 0.01 and 0.001, respectively. The red onion extract caused a reduction of about 23.22, 16.51, 14.98 and 0.38% at the concentration 1.0, 0.1, 0.01 and 0.00.1, respectively. Garlic extract at the higher concentration (1.0) reduced 89.06% of mycelial dry weight of A. niger and 38.58, 2.88 and 2.11% at the concentrations 0.1, 0.01 and 0.001, respectively. While, onion extracts promote mycelial growth of the fungus P. digitatum garlic extract at the higher concentration reduced 93.29% of mycelial dry weight of that fungus and 25.93, 2.78 and 0.47% at the other concentrations (0.1, 0.01 and 0.001, respectively). The three onion extracts showed no effect on the spore germination of A. niger , while, 2.0% of the spores of P. digitatum were germinated at the higher concentration of the yellow onion extracts. Garlic extracts completely inhibited spore germination of both fungi at the higher concentration (1.0). The three onion extracts as well as the lower concentrations (0.1, 0.01 and 0.001) of the garlic extract have no effect on both bacteria. Although, the inhibition zone of S. aureus at the lower concentration (0.1) of the garlic extract was 0.5 cm, the higher concentration (1.0) of it completely inhibited bacteria.